AMS 14C and Chemical Composition of Atmospheric Aerosols from Mexico City. Issue 2 (3rd February 2017) - Solís, C; Gómez, V; Ortíz, E; Chávez, E; Miranda, J; Aragón, J; Martínez, M A; Castro, T; Peralta, O
Abstract: Air pollution in Mexico City, which has more than 22 million inhabitants, continues to be one of the main environmental issues. Aerosol samples (PM10 ) collected in Mexico City and the city of Cuernavaca (a clean reference site) have been characterized using different techniques. This multifaceted approach addresses the source apportionment of the carbonaceous matter in PM10, as well as the airborne elements and ions. Accelerator mass spectrometry (AMS) radiocarbon analysis of total carbon, X-ray fluorescence (XRF), and ion chromatography were performed on aerosols collected at three sites in Mexico City and one site in Cuernavaca, during 2 months of the cold-dry season (November–December) in 2012. New results obtained for Mexico City are compared with previous reports. Average levels of PM10 were higher in Mexico City sites (43.3–60.8 μg/m 3 ) than in Cuernavaca (32.2 μg/m 3 ). According to the material balance, PM10 collected in Mexico City had a lower contribution of crustal material (31.2–36.8%) than Cuernavaca (46.9%). Average contributions of particulate carbonaceous matter to PM10 were similar in both cities, but much higher contributions of mineral salts, trace elements, and ions were observed in Mexico City in comparison to Cuernavaca. Total organic carbon (OC) and elemental carbon (EC) contents were higher in aerosols from Mexico City than those from Cuernavaca. The temporal variation results showed that within all locations studied the OC concentration was high compared to the EC. Results from a theoretical calculation of fossil carbon (FC) and biogenic carbon (BC) concentrations showed that FC and BC levels depend on the site: at Mexico City sites, FC was equal or higher than BC. At Cuernavaca, BC was always higher than FC.